Brain Gym Therapy For Schizophrenics Cognitive Function In Mental Hospital - Made Sumartyawati; N L Sudiarti; I M E Santosa; C Sepriana; Sukardin Sukardin (UIMA Press, 2021)
Background: The cognitive function of the patient at the Intermediate Room of RSJ Mutiara Sukma has not improved. Objectives: This study aims to determine the effect of brain exercise therapy on cognitive function in schizophrenic patients. Methods: A quasy experimental study with non-equivalent control group before and after design was performed. The population were all schizophrenic patients in the intermediate room. Incidental sampling was carried out and obtained 40 cooperative schizophrenic patients and its divided into treatment and control groups. Cognitive function was assessed using the Schizophrenia Cognitive Rating Scale (SCoRS) and the difference in effect was measured using the independent-t test with SPSS Results: The mean of cognitive function at the treatment group was 44 before and 36 after treatment, at the control group was 50 before and 47 after treatment. The p value of the Lavene test was 0,000 with a 2-tailled sig of 0.001 on the independent t-test, showed a significant difference between the cognitive function of the treatment group and the control group Conclusion: The study showed that there were different effects of brain exercise therapy on reduction of cognitive function in schizophrenia patients in the intermediate room.